(untitled) (Journal of Scientific Research, 2009)
We present here characterizations of graphs whose semi total (point) graphs are outerplanar and k-minimally nonouterplanar (k = 1, 2 or 3). Keywords: Semi total (Point) graph; Minimally nonouterplanarity; Outerplanar; Block. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2578 J. Sci. Res. 1 (3), 551-557 (2009)